FRI0216 Antibodies to recombinant 60-kd ro, 52-kd ro and 48-kd la proteins in primary sjÖgren's syndrome. usefulness of combination of analytical methods for detecting anti-ro and anti la antibodies. (1st June 2001) - Aguilera, S; Castillo, D; González, J
Abstract : Background: Objectives: To determine the reactivity and specificity of sera from primary Sjögren's syndrome (SS) patients to recombinant 60-Kd Ro, 52-Kd Ro and 48-Kd La proteins, and to correlate the results with clinical and laboratory findings. Methods: Sera from 46 patients with primary SS diagnosed according to modified 1997 European criteria, were classified in 2 groups based on the presence of anti- Ro and anti-La detected by commercial enzyme linked immunobsorbent assay (ELISA). Group A (n = 32) had anti-Ro positive sera, and group B (n = 14) had anti-Ro and anti-La negative sera, but positive antinuclear antibodies and/or rheumatoid factors. Autoantibody reactivity and specificity to recombinant 60-Kd Ro, 52-Kd Ro and 48-Kd La were analysed by ELISA and Western blot. Results: Forty-two out of 46 primary SS sera (91.30%), had reactivity to either natural or recombinant antigens or both. Anti-60-Kd Ro was found in 27 (58.69%) of all sera, of these, 22 (68.75%) sera were of group A, and 5 sera (35.71%) of group B. Anti-52-Kd Ro was highly prevalent since 38 out of 46 sera (62.60%) were positive. Among group A, 31 out of 32 (96.87%) sera were positive for 52-Kd Ro, and 7 out of 14 (50%) in group B. Anti-recombinant 48-Kd La was also highly prevalent, 38 (82.60%) of all sera were positive. In group A, 31 (96.87%) of sera were positive, while 5 (35.71%) of sera of group B, were positive. Ten (71.42%) of 14 patients of group B had antibodies for at least 1 of 3 recombinant antigens: 52-Kd Ro, 60-Kd Ro or 48-Kd La. Comparison of ELISA and Western blot produced a good intermethod agreement coefficient when anti-recombinant antibodies from sera in group A were tested: 60-Kd Ro (k = 0.563) and 52-Kd Ro (k = 0.652). Both groups were similar regarding of baseline characteristics, except that patients in group A who were younger at the time of diagnosis than those of group B (mean 39.9 v/s 63.7 years), and hipergammaglobulinemia was more frequent in group A than B. Extraglandular manifestations were similar in both groups. Conclusion: The detection of antibodies to recombinant 60-Kd Ro, 52-Kd Ro and 48-Kd La proteins, might be a new research tool as well as an aid for the diagnosis of SS, mainly in cases who are seronegative for anti-Ro or La by conventional techniques.